Your first solution▶y - 5(x) = -8
Your second solution▶y + 6x = 3
Your graphic organizer ▶-5(x) + (y) = -8;
6(x) + (y) = 3
y-intercept in the 2nd solution▶(y)= -6(x) + 3
y-intercept in the 1st solution▶-6(x)+3 - 5(x) = -8 ; - 11(x) = -11
(we get the '11x' from the 6 + 5)
x-intercept in the 1st solution▶11(x) = 11
Does 11(1) =11
▶Answer is yes, so the x-intercept is 1
➡x-intercept: 1
y-intercept should be coming up soon!
(y) = -6(1)+3
⬆ ⬆
-6 + 3 = -3
So, the y-intercept is -3
y-intercept: -3
x-intercept: 1
~in other words~
x-intercept: 1
y-intercept: -3